Prevalence and associated risk factors of overweight and obesity among adolescent population of India: a scoping review - Arpita Panda; Jayashree Parida; Susangita Jena; Swati Sukalyani Behera; Abinash Pradhan; Prasanna Kumar Patra; Sanghamitra Pati; Harpreet Kaur; Subhendu Kumar Acharya (BMC Nutrition)
Abstract Background Adolescent obesity and overweight is a global epidemic, resulting in severe health problems such as dyslipidemia, hypertension, diabetes, and coronary heart disease. With the rising prevalence of overweight and obesity among Indian adolescents, it is crucial to examine the existing status of research/evidence and the gaps in research. Therefore, the present scoping review was conducted to map the evidence on the prevalence of adolescent obesity/overweight in India and associated major risk factors. Methods The study followed Arksey and O’Malley’s (2005) scoping review framework and Joanna Briggs Institute Reviewers Manual (2015) recommendations. We undertook the literature search in electronically available databases using specific mesh terms. Results We identified 93 studies that met the standard inclusion criteria. The prevalence of overweight ranged from 1.25 to 35.8% (male: 2.6–28.1%; female: 2.7–44.5%), while obesity ranged from 0.3 to 24.6% (male: 1–19.7%; female: 0.3–32.8%). Research activity peaked between 2011 and 2020, with the highest number of publications in 2015 (n = 13). Most studies were conducted in southern states (31%), followed by eastern (16%), western (15%), and northern (12.9%) regions. A significant proportion were urban-based (70.9%) and institution-based (77.4%). Among major key risk factors, insufficient physical activity was examined in 36.5% of studies, high-calorie dietary habits in 44% of the studies, higher socioeconomic status was reported in 36.5% of studies. Additionally, 26.8% of studies explored the impact of factors like urban living, private school attendance and increased screen time as associated factors of weight gain among adolescents. Other identified factors included 12.9% reporting using vehicles for school transportation, 8.6% noting shorter sleep duration, and 17.2% recognizing a family-history of overweight and obesity as contributing factors. Conclusion The review provides a comprehensive overview of adolescent obesity and overweight in the Indian context while highlighting critical research gaps for future exploration. Most studies are cross-sectional and quantitative, underscoring the need for longitudinal and qualitative research. There is a lack of studies on gender-specific risk factors, community-based perspectives, and vulnerable populations such as slum-dwelling adolescents and school dropouts. Addressing these gaps will be essential for generating robust evidence to inform and implement effective, evidence-based policies and interventions.